PARTICIPANT SATISFACTION WITH PROFESSIONAL DEVELOPMENT IN THE ABU DHABI SCHOOL MODEL (ADSM) - Bond, Sarah (PEOPLE: International Journal of Social Sciences, 2016)
Education in Abu Dhabi is in a period of substantial reform. A key component of the reform effort is the provision of professional development (PD) for teachers. The present study examines the results of a teacher satisfaction survey given to all Tamkeen: Empowering Educators PD program participants. Areas of examination include: differences in overall satisfaction among various demographic groups of teachers (i.e., gender, grade level taught, teacher nationality (Emirati/expatriate), and demographic region); satisfaction with various program components (i.e., use of training time, organization, comprehensibility, utility, practicality, and trainer knowledge); and the relationship between participants’ satisfaction with the training time and their overall satisfaction. Findings show that there are significant differences in overall satisfaction levels among demographic groups, with male teachers, expatriate teachers, and those in the Western region having higher mean satisfaction levels than other groups. Program components with the highest satisfaction are the training venue (at school sites) and trainer knowledgeableness. Areas of lowest satisfaction are the timing for training and “overall satisfaction.” A significant relationship exists between participants’ satisfaction with the training time and their overall satisfaction. The study provides information for decision makers to enhance future program decision-making.